Effort-Reward Imbalance at Work and the Prevalence of Unsuccessfully Treated Hypertension Among White-Collar Workers. Issue 4 (6th July 2017) - Trudel, Xavier; Milot, Alain; Gilbert-Ouimet, Mahée; Duchaine, Caroline; Guénette, Line; Dalens, Violaine; Brisson, Chantal
Abstract: We examined the association between effort-reward imbalance (ERI) exposure at work and unsuccessfully treated hypertension among white-collar workers from a large cohort in Quebec City, Canada. The study used a repeated cross-sectional design involving 3 waves of data collection (2000–2009). The study sample was composed of 474 workers treated for hypertension, accounting for 739 observations. At each observation, ERI was measured using validated scales, and ambulatory blood pressure (BP) was measured every 15 minutes during the working day. Unsuccessfully treated hypertension was defined as daytime ambulatory BP of at least 135/85 mm Hg and was further divided into masked and sustained hypertension. Adjusted prevalence ratios and 95% confidence intervals were estimated. Participants in the highest tertile of ERI exposure had a higher prevalence of unsuccessfully treated hypertension (prevalence ratio = 1.45, 95% confidence interval: 1.16, 1.81) after adjustment for gender, age, education, family history of cardiovascular diseases, body mass index, diabetes, smoking, sedentary behaviors, and alcohol intake. The present study supports the effect of adverse psychosocial work factors from the ERI model on BP control in treated workers. Reducing these frequent exposures at work might lead to substantial benefits on BP control at the population level.